ASTM static tensile tests with geometric imperfections - Ng, Yi He (Nanyang Technological University, 2023)
The ASTM static tensile test with geometric imperfections, FYP B217, is the subject of this review. This research and experiment make use of aluminium 6061-T6 with geometrical imperfections. The geometrical imperfection introduced will be a hole in the middle of the static test specimen. The author reviewed previous reports from previous years and became familiar with the ASTM Standards. The definition of the mechanical properties of Aluminium 6061-T6 is the goal of this project. Computer Numerical Control (CNC) wire cutting is used to create the specimen, and the experiment is carried out in the transverse direction, just like in the previous FYP. In contrast to past conclusive year projects, the writer makes changes to the example aspects. The ASTM E8/E8M standard will be used in the specimen's design and fabrication. The most common destructive test for measuring a material's mechanical properties, such as its modulus of elasticity, yield strength, and ultimate tensile strength, is the static tensile test. To plot the stress-strain curve, raw data will be gathered following the test. The findings will be examined and contrasted with previous FYP findings. Moreover, this report will be a future reference for Aluminium 6061-T6 with geometric imperfections. The objective of this project will be to improve the experimental procedure so that reliable and consistent results can be obtained. Finally, the recommendations for static tensile tests will be discussed, and the purpose of this report is to serve as a reference for future research on Aluminium 6061-T6 with geometric imperfections.